Switching Power Universality in Unipolar Resistive Switching Memories - Kim, Jongmin (Sci Rep, 2016)
We investigate the resistive switching power from unipolar resistive switching current-voltage characteristics in various binary metal oxide films sandwiched by different metal electrodes, and find a universal feature (the so-called universality) in the switching power among these devices. To experimentally derive the switching power universality, systematic measurements of the switching voltage and current are performed, and neither of these correlate with one another. As the switching resistance (R) increases, the switching power (P) decreases following a power law P ∝ R(−β), regardless of the device configurations. The observed switching power universality is indicative of the existence of a commonly applicable switching mechanism. The origin of the power universality is discussed based on a metallic filament model and thermo-chemical reaction.